Hubungan Kejadian Demam Berdarah Dengue( DBD) Berdasarkan Faktor Lingkungan Dan Faktor Perilaku Masyarakat - Retroningrum, Della; Barus, Linda; Masra, Ferizal; Indarti, Suami (Universitas Malahayati Bandar Lampung, 2024)
Background: Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus, transmitted through the bite of the Aedes aegypti mosquito. Purpose: To determine the relationship between environmental factors and community behavioral factors with the incidence of dengue fever in the Gedong Tataan Community Health Center Working Area, Gedong Tataan District, Pesawaran Regency. Methods: This research is an analytical type with a case control approach, with a sample size of 136 respondents consisting of 68 case respondents and 68 control respondents. The data analysis used was the Chi Square test.Results: The results of the bivariate analysis revealed that there was a statistically significant relationship between the availability of lids on containers (p-value: 0.000), the frequency of landfill drainage (p-value: 0.000), the number of plants in the home environment (p-value: 0.001), the habit of hanging clothes (p-value: 0.000), the habit of using mosquito repellent (p-value: 0.000), the habit of burying used goods (p-value: 0.041) with the incidence of dengue fever, and there is no statistically significant relationship between the presence of larvae-eating fish. (p-value: 0.174), the habit of napping at 09.00-10.00 and 16.00-17.00 2022 (p-value: 0.301) with the incidence of dengue fever.Conclusion: With the results above, there is a statistically significant relationship between the availability of lids on containers, the frequency of landfill drainage, the number of plants in the home environment, the habit of hanging clothes, the habit of using mosquito repellent/anti-mosquitoes, the habit of burying used items. Recommendations: For the Gedong Tataan Community Health Center are to encourage the community through outreach activities to always cover the landfill, drain the landfill at least ≥1 a week, keep larvae-eating fish, look after and care for plants, avoid the habit of hanging clothes in the house, avoid sleeping at midnight. 09.00-10.00 and 16.00-17.00, use mosquito repellent/anti-mosquito and bury used items that can collect rainwater. Keyword : DHF, Environment, Mosquitoes, Behavior ABSTRAK Latar Belakang: Demam berdarah dengue (DBD) merupakan penyakit infeksi yang disebabkan oleh virus dengue, ditularkan melalui gigitan nyamuk Aedes aegypti.Tujuan: Untuk mengetahui hubungan faktor lingkungan dan faktor perilaku masyarakat dengan kejadian DBD di Wilayah Kerja Puskesmas Gedong Tataan Kecamatan Gedong Tataan Kabupaten Pesawaran.Metode: Penelitian ini merupakan jenis analitik dengan pendekatan case control, dengan jumlah sampel 136 responden terdiri dari 68 responden kasus dan 68 responden kontrol. Analisis data yang digunakan adalah uji Chi Square.Hasil: Hasil analisis bivariat diketahui adanya hubungan yang signifikan secara statistik antara ketersediaan tutup pada kontainer (p-value : 0,000), frekuensi pengurasan TPA (p-value : 0,000), banyaknya tanaman di lingkungan rumah (p- value : 0,001), kebiasaan menggantung pakaian (p-value : 0,000), kebiasaan menggunakan obat/anti nyamuk (p-value : 0,000), kebiasaan mengubur barang bekas (p-value : 0,041) dengan kejadian DBD, serta tidak ada hubungan yang signifikan secara statistik antara keberadaan ikan pemakan jentik (p-value : 0,174), kebiasaan tidur siang pada pukul 09.00-10.00 dan pukul 16.00-17.00 2022 (p-value : 0,301) dengan kejadian DBD.Kesimpulan: Dengan hasil di atas adanya hubungan yang signifikan secara statistik antara ketersediaan tutup pada container, frekuensi pengurasan TPA, banyaknya tanaman di lingkungan rumah, kebiasaan menggantung pakaian, kebiasaan menggunakan obat/anti nyamuk, kebiasaan mengubur barang bekas.Saran: Bagi pihak puskesmas Gedong Tataan untuk dapat menghimbau masyarakat melalui kegiatan penyuluhan untuk selalu memberi tutup pada TPA, melakukan pengurasan TPA minimal ≥1 dalam seminggu, memelihara ikan pemakan jentik, menjaga dan merawat tanaman, menghindari kebiasaan menggantung pakaian didalam rumah, menghindari tidur pada jam 09.00-10.00 dan 16.00-17.00, menggunakan obat/anti nyamuk dan mengubur barang bekas yang dapat menampung air hujan. Kata Kunci: DBD,Lingkungan, Nyamuk, Perilaku